Site-specific incubations reveal biofilm diversity and functional adaptations in deep, ancient desert aquifers - Atencio, Betzabe; Malavin, Stas; Rubin-Blum, Maxim; Ram, Roi; Adar, Eilon; Ronen, Zeev (Frontiers in Microbiology, 2025)
Deep pristine aquifers are ecological hotspots with diverse microbial life, where microorganisms exist either attached (sessile) to solid substrates or suspended in groundwater (planktonic). Characterizing the attached microbial communities is of paramount importance, especially in the context of biofouling. However, obtaining samples of attached microbes that thrive under natural (undisturbed) conditions is challenging. Our study addresses this by retrieving sessile microbes on-site. We installed columns filled with site-specific rock cuttings at the wellhead, allowing fresh groundwater to flow continuously for approximately 60 days. We hypothesized that the attached microbial communities would differ structurally from planktonic microbes due to the aquifer’s lithological and mineralogical composition. This study involved an exploratory examination of the microbial communities in different aquifers with distinct mineralogies, including quartzitic sandstone, calcareous, chert, and highly heterogeneous (clastic) aquifers in Israel’s Negev Desert. Metagenomic analysis revealed both shared and distinct microbial communities among attached and planktonic forms in the various environments, likely shaped by the aquifers’ physical, lithological, and mineralogical properties. A wealth of carbon-fixation pathways and energy-conservation strategies in the attached microbiome provide evidence for the potential productivity of these biofilms. We identified widespread genetic potential for biofilm formation (e.g., via pili, flagella, and extracellular polymeric substance production) and the interactome (e.g., quorum-sensing genes). Our assessment of these functions provides a genomic framework for groundwater management and biofouling treatment.